Replacement of conventional aggregates and fillers with steel slag and palm kernel shell ash in dense-graded asphalt mixtures - David A. Azong-bil; Ebenezer D. A. Barnor; Kenneth A. Tutu; Collins A. Nketiah (Journal of Sustainable Construction Materials and Technologies)
Large quantities of steel slag and palm kernel shell ash (PKSA) – waste products from steel production and palm oil milling, respectively – are generated annually in severalcountries, and their disposal is challenging. Meanwhile, the over-reliance on conventional rock aggregates for asphalt mixture production poses increasing sustainability challenges. This study investigated the potential of entirely replacing granite aggregates with steel slag and PKSA in a dense-graded asphalt mixture. Two sets of asphalt mixtures were prepared; the control mixture contained crushed granite aggregate and hydrated lime, while the other set incorporated steel slag as coarse aggregate and PKSA as fine aggregate and filler. Both mixture types utilized AC-30 viscosity-graded asphalt binder. The properties of the waste materials met the quality standards required for aggregates in asphalt mixture production. Both mixture types were designed according to the Marshall design procedure and were evaluated for durability (Cantabro abrasion loss), fatigue cracking Resistance, rutting Resistance, and moisture damage susceptibility. The Cantabro abrasion loss test indicated that the waste-based mixture was 3% less durable than the control. However, the cracking Resistance of the waste-based mixture was approximately twicethat of the control. Even though the rapid rutting test indicated that the control mixture was slightly superior in rutting Resistance, the Marshall quotient suggested otherwise. Both mixture types exhibited similar moisture damage resistance. Overall, the steel slag and PKSA samples have shown high potential to replace virgin granite aggregates and lime in asphalt mixtures fully and are, thus, recommended for field performance evaluation and possible adoption.